Políticas públicas de acesso à educação superior, beneficiários, objetivos e resultados, em Vitória da Conquista: FIES e PROUNI - Farias, Abmael da Cruz (2010)
The objective of this paper is to study public policies regarding higher education, beneficiaries, objectives, and results in Vitória da Conquista, Bahia for the year of 2008: FIES (Student Loans Program) and PROUNI (Program of Higher Education for All). This paper focuses on undergraduate studies and attempts to evaluate these programs in terms of their efficiency and effectiveness as they have facilitated access for millions of Brazilians with repercussions pertaining to students´ income and availability of financial resources. This assessment is unprecedented and aims at producing data for these programs. Findings can be used by decision makers, both to draw up and implement policies, as well as by the program beneficiaries. This study raises the hypothesis that these programs have been both effective and efficient in democratizing students´ access to higher education by considering them as citizens or consumers, a situation that was made possible with the democratization of educational services to higher education institutions. These ideas were confirmed by this research through analysis of the documentation of the education institutes participating in the study, information posted on their official websites, and applied questionnaires. Therefore, this study is exploratory in nature and incorporates information collected through literature as well as documentation from which both quantitative and qualitative data were produced. Debates around this issue rise from the analysis of the relationship between public and private spaces and also involve issues related to social justice, democratization of opportunities, citizenship, and gratuity on the one hand and consumption and payment on the other hand, all related to higher education